2021
DOI: 10.1007/s11033-021-06537-0
|View full text |Cite
|
Sign up to set email alerts
|

TCF7L2 gene polymorphism as a risk for type 2 diabetes mellitus and diabetic microvascular complications

Abstract: Background: Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic condition with various genetics and environmental in uences that affects the capacity of the body to produce or use insulin resulting in hyperglycemia, which may lead to variable complications. It is one of the world's rising health problems.There is emerging evidence that some genetic polymorphisms can impact the risk of evolving T2DM.We try to determine the relationship of (rs7903146) variant of the Transcription factor 7-like 2 (TCF7L2) gene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…Also, TT and CT genotypes were significantly increased in the T2DM without complications and T2DM with complications groups. [ 27 ] The same is also evidenced by Nanfa et al . [ 28 ] and Demirsoy et al ,[ 29 ] who have reported that the T allele at rs7903146 is related to the risk of T2DM.…”
Section: Discussionsupporting
confidence: 77%
“…Also, TT and CT genotypes were significantly increased in the T2DM without complications and T2DM with complications groups. [ 27 ] The same is also evidenced by Nanfa et al . [ 28 ] and Demirsoy et al ,[ 29 ] who have reported that the T allele at rs7903146 is related to the risk of T2DM.…”
Section: Discussionsupporting
confidence: 77%
“…T2DM has become one of the serious public health problems. T2DM is the result of the interaction between genetic and environmental factors, a large number of studies have revealed that multiple single nucleotide polymorphisms (SNPs) are related to the development of T2DM [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%